Phosphorus recovery from simulated municipal wastewater (SMW) through the crystallization of magnesium ammonium phosphate hexahydrate (MAP). Issue 8 (23rd February 2017) - Mpountas, Ioannis; Papadakis, Emmanuel; Koutsoukos, Petros
Abstract: BACKGROUND: Phosphorus and nitrogen recovery from municipal and/or industrial wastewater treatment plants in the form of magnesium ammonium phosphate hexahydrate (MgNH4 PO4 ·6H2 O, MAP, Struvite) is an attractive alternative for the valorization of wastes. Although efforts have been focused on the recovery of nitrogen and phosphorus nutrients from wastewater at alkaline pH, removal of these nutrients in weakly acid pH is still challenging. The advantage of acid pH is that the precipitation of heavy metals in the form of insoluble hydroxides is avoided provided that their concentrations are relatively low. RESULTS: The metastable zone width of solutions, supersaturated with respect to MAP at pH 6.50 was investigated. The kinetics of MAP formation both in unseeded and in seeded solutions was investigated in batch reactors at constant supersaturation. The rates of crystal growth of MAP on seed crystals showed a parabolic dependence on the relative supersaturation. The concentration of the inoculating seed crystals affected the rates of crystal growth. CONCLUSIONS: It is possible to crystallize MAP at pH values of 6.50 provided that the supersaturation is sufficient. From the rate dependence on relative supersaturation (parabolic) it was concluded that the crystal growth mechanism was surface diffusion controlled for the integration of the growth units at the active crystal growth sites. Secondary nucleation, depending on the solution supersaturation, was observed within the stable domain of the metastable zone. The morphology of MAP seed crystals remained unchanged, while the mean particle size increased reaching comparable sizes irrespective of the degree of supersaturation. © 2017 Society of Chemical Industry